Representing dementia: A qualitative analysis of how people affected by dementia situate themselves in relation to different dementia discourses - Putland, Emma (2022)
Dementia remains widely feared and stigmatised in contemporary society. Popular representations commonly reduce dementia to either concerns surrounding ageing, degeneration and death, or to an overly positive discourse of ‘living well’, both of which can present unrealistic expectations and socially distance people with dementia. Against this, individuals directly affected by dementia can provide more nuanced accounts that engage with multiple discourses and better reflect dementia’s complexity. Further qualitative exploration of these first-hand accounts is urgently required.